Cerebrovascular Function in the Large Arteries Is Maintained Following Moderate Intensity Exercise - Steventon, Jessica J.; Hansen, Alex B.; Whittaker, Joseph R.; Wildfong, Kevin W.; Nowak-Flück, Daniela; Tymko, Michael M.; Murphy, Kevin; Ainslie, Phil N. (Frontiers in Physiology, 2018)
Exercise has been shown to induce cerebrovascular adaptations. However, the underlying temporal dynamics are poorly understood, and regional variation in the vascular response to exercise has been observed in the large cerebral arteries. Here, we sought to measure the cerebrovascular effects of a single 20-minute session of moderate-intensity exercise in the one hour period immediately following exercise cessation. We employed transcranial Doppler ultrasonography to measure cerebral blood flow velocity in the middle cerebral artery (MCAv) and posterior cerebral artery (PCAv) before, during, and following exercise. Additionally, we simultaneously measured cerebral blood flow in the internal carotid artery (ICA) and vertebral artery (VA) before and up to one hour following exercise cessation using Duplex ultrasound. A hypercapnia challenge was used before and after exercise to examine exercise-induced changes in cerebrovascular reactivity. We found that MCAv and PCAv were significantly elevated during exercise (p = 4.81 x 10-5 and 2.40 x 10-4 respectively). A general linear model revealed that these changes were largely explained by the partial pressure of end-tidal CO2 and not a direct vascular effect of exercise. After exercise cessation, there was no effect of exercise on cerebral blood flow velocity or cerebrovascular reactivity in the intracranial or extracranial arteries (all p > 0.05). Taken together, these data confirm that cerebral blood flow is rapidly and uniformly regulated following exercise cessation in healthy young males.